PENGGUNAAN MEDIA GOOGLE FORM DALAM UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN SENI BUDAYA - Gusti Ayu Made Puspawati; Ni Komang Sri Rahayu (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
This study aims to improve student learning outcomes, as well as the response and impact of the application of Google Form media in the Cultural Arts subject for class X AP 2 SMK PGRI 1 Badung in the 2020/2021 school year. This Google Form media is a google docs service that can be used for surveys, invitations, attendance, online quizzes. Google Form media is used to increase students' interest in learning so that if students' interest in learning increases, student learning outcomes also increase. The results showed that before the application of Google Form media the average value was 69.5. After the application of Google Form media the average became 85.17 with 100% classical completeness in the first cycle which showed a significant increase of 17.01. The results of observing student responses before using Google Form media with an average of 67.27. After using Google Form the average becomes 86.6. Based on the results obtained, it can be said that the application of Google Form media has succeeded in improving learning outcomes in the subjects of Cultural Arts for class X AP2 SMK PGRI 1 Badung for the 2020/2021 school year.